2013
DOI: 10.2478/eces-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varied NPK Fertilization on Catalase Activity of Amaranth (Amaranthus Cruentus L.)

Abstract: Abstract:A study was carried out on the effect of varied NPK fertilization on catalase activity per gram fresh weight of the leaves of two varieties of amaranth, Rawa and Aztek, at different developmental stages (seedling, five-leaf, flowering and mature seed), as well as in the seeds. Amaranth was grown in a field experiment in southeast Poland, at wide-row spacing on good wheat complex soil. The following combinations of macronutrient levels were applied: I -50 kg N · ha . The study showed that catalase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…1 Veeru and others (); 2 Repo‐Carrasco‐Valencia (2009); 3 Klimczak and others (); 4 Morrison and Twumasi (); 5 Queiroz and others (); 6 Kunyanga and others (2011); 7 Kunyanga and others (); 8 Skwaryło‐Bednarz and Krzepiłko (); 9 Amin and others (); 10 Zeashan and others (); 11 Mošovska and others (); 12 Odukoya and others (); 13 Paśko and others (); 14 Paśko and others (); 15 López and others (); 16 Oboh and others (); 17 Khandaker and others (); 18 Ali and others (); 19 Gorinstein and others (); 20 Asao and Watanabe (; 21 Ogrodowska and others (); 22 Gamel and others (); 23 Alvarez‐Jubete and others (); 24 Tikekar and others (); 25 Ozsoy and others (); 26 Adebooye and others (; 27 Conforti and others (); 28 Conforti and others (); 29 Pacifico and others (); 30 Cai and others (); 31 Jung and others (); 32 Chlopicka and others (); 33 Rao and others (); 34 Adefegha and Oboh (); 35 – Kraujalis and Venskutonis (b); 36 Milán‐Carrillo and others ().…”
Section: Antioxidant Potential Of Amaranthmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Veeru and others (); 2 Repo‐Carrasco‐Valencia (2009); 3 Klimczak and others (); 4 Morrison and Twumasi (); 5 Queiroz and others (); 6 Kunyanga and others (2011); 7 Kunyanga and others (); 8 Skwaryło‐Bednarz and Krzepiłko (); 9 Amin and others (); 10 Zeashan and others (); 11 Mošovska and others (); 12 Odukoya and others (); 13 Paśko and others (); 14 Paśko and others (); 15 López and others (); 16 Oboh and others (); 17 Khandaker and others (); 18 Ali and others (); 19 Gorinstein and others (); 20 Asao and Watanabe (; 21 Ogrodowska and others (); 22 Gamel and others (); 23 Alvarez‐Jubete and others (); 24 Tikekar and others (); 25 Ozsoy and others (); 26 Adebooye and others (; 27 Conforti and others (); 28 Conforti and others (); 29 Pacifico and others (); 30 Cai and others (); 31 Jung and others (); 32 Chlopicka and others (); 33 Rao and others (); 34 Adefegha and Oboh (); 35 – Kraujalis and Venskutonis (b); 36 Milán‐Carrillo and others ().…”
Section: Antioxidant Potential Of Amaranthmentioning
confidence: 99%
“…The TAC of amaranth depended on the plant variety (“Rawa” and “Aztek”) and on the doses of the NPK fertilizer; dependencies between TAC of the soils and leaves and the levels of NPK, as well as between the TAC of the soil and of amaranth leaves were shown by the statistical data analysis (Skwaryło‐Bednarz and Krzepiłko ).…”
Section: Antioxidant Potential Of Amaranthmentioning
confidence: 99%
“…Plants significantly contribute and mediate C translocation belowground, via the roots and into the rhizosphere (Lakshmanan et al, 2014). This introduction can influence soil heterotrophic respiration, microbial community composition and activity (Hinsinger et al, 2009;Ai et al, 2013;Skwarylo-Bednarz and Krzepilko, 2013;Nie et al, 2014). By sampling at two proximities away from the root system of spring wheat, the ability of the rhizosphere to shape bacterial communities was assessed.…”
Section: Response Of Bacterial Communities At Experimental Harvestmentioning
confidence: 99%
“…Hence, the type of aboveground vegetation and its cultivation practices undoubtedly play an important role in modeling soil biological features. It should be noted that not all plant species exert positive influence on the growth, abundance and activity of soil microflora [Skwaryło-Bednarz 2008]. On the contrary, numerous scientific studies have confirmed that certain plant species may have a negative effect on soil microorganisms through their root exudates.…”
Section: Introductionmentioning
confidence: 99%
“…The seeds turned out to be of high nutritional value [Skwaryło-Bednarz et al 2020]. Several literature reports concerning the influence of amaranth on the activity of soil microflora have demonstrated that this plant has stimulating properties [Skwaryło-Bednarz 2008], probably due to the amaranth cultivation practices, not requiring chemical protection methods. It is possible due to the soil and climatic conditions of Poland, particularly unfavorable for the spread of amaranth -specific phytopatogens, which results in the absence of pest colonization [Skwaryło-Bednarz and Nalborczyk 2006].…”
Section: Introductionmentioning
confidence: 99%